The Problematic of the Amazonian Peoples from the Perspective of the Social Doctrine of the Church - Gutiérrez Velasco, Flavio (2018)
This paper deals with the problems regarding the human rights of the Amazonian peoples of Peru, which are not respected mainly due to a neoliberal andconsumeristic policy that seeks only profit. This problem is approached from a humanistic and social doctrine of the Churchu perspective, in the context of thevisit that Pope Francis made to Peru from January 18 to 21, 2018.